Does parenting moderate the association between adverse childhood experiences and adolescents’ future orientation? - Chainey, Carys; Burke, Kylie; Haynes, Michele (My University, 2022)
Adolescents who think and act towards the future are more likely to thrive. This future orientation may, however, be affected by adversity and the parenting they receive. The influence of cumulative adversity, and of parenting in the context of adversity, is yet to be explored. We investigated whether adolescents’ future orientation is associated with experiences of singular and multiple types of adversity, and if parenting moderates these associations. Data from the Longitudinal Study of Australian Children K Cohort (n = 1177; 51.5% male; aged 16–17 years) were used to measure future orientation at age 16–17, the number of adversities experienced from age 4/5 to age 14/15 (parental separation and divorce, household substance use problem, household mental health condition, domestic violence), and parenting received at age 14/15 (warmth, hostility, communication, monitoring). Relationships and moderations were tested using stepwise moderated logistic regression analyses, controlling for demographic characteristics. Adolescents were at risk for low future orientation if they had experienced singular or multiple types of adversity, higher hostility, lower communication, and lower monitoring. We did not find a moderating effect of parenting. These results indicate that while young people are less likely to have future-related thoughts and actions if they have experienced singular or multiple types of adversity, their future orientation may be supported by effective parenting and non-hostile parent-adolescent relationships. Young people who experience both adversity and poor parenting may be at higher risk than others. Further investigation is warranted, to explore the causal relationships between adverse experiences, parenting, and future orientation.
Journal of Child and Family Studies
Keywords: Adolescents and youth; Disadvantage, adversity and resilience; Childhood and child development; Families and relationships